THE ROLE OF THE STATE AND THE INTERNATIONAL COMMUNITY IN THE FIGHT AGAINST POVERTY IN UZBEKISTAN - Yormatov Ilmidin Toshmatovich (Web of Journals Publishing, 2023)
Poverty is one of the serious social problems faced by many countries, including Uzbekistan. Despite significant progress in economic development, uneven distribution of income and social resources remains one of the main causes of poverty in the country. In this article, we will consider the main factors, ways of fighting against poverty and the measures taken by the government of Uzbekistan to solve this problem.
Keywords: poverty, national, international, GDP, poverty line, macroeconomic policy, diversification, consumption basket, international organizations, welfare state.